Features of Formation and Functioning in the Psyche of the Subject of the Mechanism of Substitution (Psycho-Correction Function of Pets) - Perepeliuk, T.; Traverse, T.; Dziubenko, I.; Tkachuk, M. (International Journal of Psychosocial Rehabilitation, 2019)
Depth psychology explains many points in a person’s life. Man shares his place in society with animals. But we have never thought about how they affect us, and whether they affect us at all, why we choose this animal only, not another one, and whether we should have a pet at all. Because this problem is very little covered in depth psychology, we found it interesting. This problem is relevant nowadays - a time when people suffer from loneliness, misunderstandings, conflicts and difficulties in the family.